PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN DAN KEJELASAN SASARAN ANGGARAN TERHADAP SENJANGAN ANGGARAN INSTANSI PEMERINTAH DAERAH DENGAN ASIMETRI INFORMASI, GROUP COHESIVENESS, BUDAYA ORGANISASI DAN KECUKUPAN ANGGARAN SEBAGAI VARIABEL MODERASI - Benediktus Oksanda; Emrinaldi Nur DP; Julita - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Public sectors use performance-based budgeting system that is an efficient and participative development process, and use performance as a benchmark for the achievement of local government’s budgeting target. However, then performance-based assessment motivates agents to perform budgetary slack for the sake of a better future career. The purpose of this research is to explore the influence of budgeting participation and budget goal clarity on budgetary slack with information asymmetry, group cohesiveness, organizational culture and budget adequacy as moderating variables.The population of this research was 26 SKPD offices of Pekanbaru City. This research used purposive sampling with the final sample of 95 participants. This research used primary data by disseminating the questionnaire at 26 SKPD offices of Pekanbaru City. Multiple linear regression and MRA was used in this research as technical analysis to test the hypothesis. The results of this research showed that budgetary participation and budget goal clarity significantly influenced budgetary slack. Group cohesiveness as a moderating variable was able to influence the relationship between budgetary participation and budgetary slack. In the meanwhile, information asymmetry, organizational culture, and budget adequacy were unable to affect the relationship between budgetary participation and budgetary slack. Information asymmetry, organizational culture, and budget adequacy could only influence the relationship between budget goal clarity and budgetary slack. At the same time, group cohesiveness was unable to influence the relationship between budget goal clarity and budgetary slack.Keywords: Budgetary Participation, Budget Goal Clarity, Information Asymetry, Group Cohesiveness, Organizational Culture, Budget Adequacy, Budgetary Slack